Wybrane problemy szacowania poziomu ryzyka informatycznego w bankowości spółdzielczej - Wawrzyniak, Dariusz; Myrczek, Józef (Chosen aspects of information technology risk assessment in co-operative banking, 2006)
The article presents chosen aspects of information technology in co-operative banking. The main areas of the IT risk were pointed out. Chosen Basel Committee documents were also presented as well as their influence on the risk management process. The necessity of using the quantitative methods was emphasized. The authors presented the general classification of the methods and described some of them pointing out the possibilities for taking the advantage of the methods in co-operative banking. Very important part of the article deals with behaviour of IT systems’ users and its influence on the systems security. The authors described selected methods allowing monitoring of users’ activities. The main focus was set on the immunological methods and the methods based on the Markov processes. Some easy mathematical models were also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 81-100